Dynamics of Economic Management in the Context of Non-Formal Education: An Analysis of Resource Management for the Sustainability of Education Programs - Enni Sustiyatik; Tontowi Jauhari; Sachin Gupta (Universitas Negeri Semarang, 2023)
Non-formal education is playing an increasingly important role in providing learning opportunities for individuals from diverse backgrounds. However, the sustainability of these programs often depends on the efficiency of sound economic management. This abstract discusses an in-depth analysis of how economic management influences the overall dynamics of non-formal education. This research includes identifying the financial resources needed to manage operations, training, facilities, and program development. The main focus is identifying best practices in fund allocation, sustainable financing, and effective expenditure monitoring. Using a case study approach, this study analyzes various non-formal education programs operating in different environments. The results of the analysis show that there is a need for a good balance between operational costs, learning quality, and the availability of funds for long-term development. In this context, creative approaches such as partnerships with the private sector, funding from philanthropic institutions, and using technology to reduce costs are all key factors. In addition, this research encourages the existence of a framework that supports transparency, accountability, and effective risk management in the economic aspects of non-formal education. By combining these aspects, non-formal education can optimize its social impact while ensuring program continuity through sustainable economic management. In conclusion, this research provides in-depth insight into how economic management plays a crucial role in ensuring non-formal education remains relevant and sustainable. By analyzing the economic factors that affect non-formal education, this study proposes strategies and recommendations that can assist decision makers in developing non-formal education programs that are financially successful and socially beneficial